2018
DOI: 10.1007/s00125-018-4690-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a missense variant in the WFS1 gene that causes a mild form of Wolfram syndrome and is associated with risk for type 2 diabetes in Ashkenazi Jewish individuals

Abstract: We have identified a low-frequency coding variant in the WFS1 gene that is enriched in Ashkenazi Jewish individuals and causes a mild form of Wolfram syndrome characterised by young-onset diabetes and reduced penetrance for optic atrophy. This variant should be considered for genetic testing in individuals of Ashkenazi ancestry diagnosed with young-onset non-autoimmune diabetes and should be included in Ashkenazi carrier screening panels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 41 publications
(71 reference statements)
2
45
1
Order By: Relevance
“…Our other important finding is the high prevalence of nonsyndromic WFS1 cases, much more common than WS and comparable with that reported in consanguineous families in Lebanon (11), in a nonconsangineous population. Nonsyndromic diabetes has also been reported with homozygosity for a nonsynonymous variant frequently found in Ashkenazi Jewish individuals (20), but it is clearly not confined to that variant. The therapeutic implications of this diagnostic reassignment remain to be seen, but successful use of incretin interventions has been reported (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Our other important finding is the high prevalence of nonsyndromic WFS1 cases, much more common than WS and comparable with that reported in consanguineous families in Lebanon (11), in a nonconsangineous population. Nonsyndromic diabetes has also been reported with homozygosity for a nonsynonymous variant frequently found in Ashkenazi Jewish individuals (20), but it is clearly not confined to that variant. The therapeutic implications of this diagnostic reassignment remain to be seen, but successful use of incretin interventions has been reported (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in WFS1 gene are responsible for most WFS patients. Since the discovery of WFS1 in 1998, more than 300 different mutations have been identified in this gene [34] and majority of them located in the exon 8 encoding the nine transmembrane segments and the C-terminal tail of wolframin [33]. In this study, we found four missense mutations located in exon 8 of WFS1 , two of them were first reported including c.1618 T > G (p.Trp540Gly) and c.1048 T > A (p.Phe350Ile).…”
Section: Discussionmentioning
confidence: 99%
“…Patient # 8 presented with asymptomatic optic atrophy (correctable vision loss) and was identified to have a pathogenic variant ( WFS1 c.1941C>A; p.Cys647) [38,39] and a VUS (c.1597C>T; p.Pro533Ser) in trans (Table 1) [40]. Patient # 97 had bilateral vision loss and was homozygous for a missense variant (c.1672C>T; p.Arg558Cys) [41,42]. At 33 and 39 years of age, respectively, neither individual had diabetes nor hearing loss, two of the canonical features of Wolfram syndrome.…”
Section: Discussionmentioning
confidence: 99%